1992
DOI: 10.1038/clpt.1992.179
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rilmenidine on tests of autonomic function in humans

Abstract: The effects of rilmenidine, a new centrally acting antihypertensive agent, on a number of tests of autonomic function were investigated in six healthy male volunteers. Baroreflex function (delta RR interval [in milliseconds] with each millimeter of mercury change in systolic blood pressure) was determined in response to changes in pressure after injections of phenylephrine and nitroglycerin. Reflex cardiovascular responses to handgrip and standing, as well as during deep breathing and the Valsalva maneuver, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Overall, our findings in hypertensive patients support the view that both rilmenidine and atenolol attenuate sympathetic and enhance cardiac parasympathetic tone as previously shown in normotensive volunteers [10,26].…”
Section: Autonomicfunction Testssupporting
confidence: 79%
See 1 more Smart Citation
“…Overall, our findings in hypertensive patients support the view that both rilmenidine and atenolol attenuate sympathetic and enhance cardiac parasympathetic tone as previously shown in normotensive volunteers [10,26].…”
Section: Autonomicfunction Testssupporting
confidence: 79%
“…been shown that rilmenidine exerts similar effects in Double-blind comparative studies vs atenolol, hydroexperimental animals [8,9]. Furthermore, in normal activity, rilmenidine enhanced parasympathetic tone as assessed by heart rate (HR) changes immediately after standing and deep breathing and blunted the reflex increase in sympathetic activity after standing for 3 min [10]. However, these effects have not been reported so far in hypertensive patients.…”
Section: Introductionmentioning
confidence: 90%
“…Рилменидин имеет большее сродство с имидазолиновыми рецепторами [16]. По сравнению с клонидином, он более эффективно снижает АД, а число нежелательных явлений наблюдается намного реже [17]. При сравнении рилменидина с атенололом, первый вызывал такое же снижение АД‚ но переносимость его оказалась лучше.…”
Section: симпатолитики центрального действия альфаадреноблокаторыunclassified
“…These arrhythmias usually occur in patients with left ventricular hypertrophy. They may result in sudden death 11–14 …”
Section: Central Anti‐arrhythmic Effectsmentioning
confidence: 99%